3-Arylpropionylhydroxamic acid derivatives as Helicobacter pylori urease inhibitors: Synthesis, molecular docking and biological evaluation. Issue 19 (1st October 2016) - Shi, Wei-Kang; Deng, Rui-Cheng; Wang, Peng-Fei; Yue, Qin-Qin; Liu, Qi; Ding, Kun-Ling; Yang, Mei-Hui; Zhang, Hong-Yu; Gong, Si-Hua; Deng, Min; Liu, Wen-Run; Feng, Qiu-Ju; et al.
Graphical abstract: Highlights: 3-Arylpropionylhydroxamic acid derivatives showed a mixed inhibition mechanism. Mixed urease inhibitors with enhanced inhibitory activities have been synthesized. Urea showed substrate inhibition against H. pylori urease. Abstract: Helicobacter pylori urease is involved in several physiologic responses such as stomach and duodenal ulcers, adenocarcinomas and stomach lymphomas. Thus, inhibition of urease is taken for a good chance to treat H. pylori -caused infections, we have therefore focused our efforts on seeking novel urease inhibitors. Here, a series of arylpropionylhydroxamic acids were synthesized and evaluated for urease inhibition. Out of these compounds, 3-(2-benzyloxy-5-chlorophenyl)-3-hydroxypropionylhydroxamic acid (d24 ) was the most active inhibitor with IC50 of 0.15 ± 0.05 μM, showing a mixed inhibition with both competitive and uncompetitive aspects. Non-linear fitting of kinetic data gives kinetics parameters of 0.13 and 0.12 μg·mL −1 for K i and K i ′, respectively. The plasma protein binding assays suggested thatd24 exhibited moderate binding to human and rabbit plasma proteins.